Menakar Keberlanjutan Pasar Tiban: Persepsi Stakeholder, Analisis SWOT dan Kebijakan Hukum: (Studi Kasus di Kota Pekalongan) - Rismawati, Shinta Dewi; Baihaqi T, Irham; Thoha, Silvia Milady Azkiya; Linuwih, Sugesti Sri; Sumbogo, Yuliarto Joko; Sasongko, Supomo Ari (Indra Institute Research & Publication, 2025)
This paper aims to map the public perception of the existence of pop up markets in driving the local economy and to explain the SWOT analysis of the prospects for the sustainability of pop up markets in Pekalongan City. The research used a qualitative approach by using primary data sources and secondary data sources. Primary data was obtained through in-depth interviews with stakeholders which were determined by purposive sampling and observation. Secondary data sources were obtained from library studies. The data obtained was then analysed using an interactive model. The findings show that the perception of stakeholders about the existence of the tiban market in driving the local economy is quite diverse although some assess it negatively, but most of the public thinks that the existence of the tiban market is considered positive. Meanwhile, from the SWOT analysis, the existence of pop up markets to drive the local economy in Pekalongan City is considered quite prospective with several requirements that must be met, including strengthening synergy and cooperation between stakeholders and providing adequate attributes and legal policies.